(untitled) (Swiss Medical Weekly, 2024)
BACKGROUND: Lipoprotein (a) [Lp(a)] serum levels are highly genetically determined and promote atherogenesis. High Lp(a) levels are associated with increased cardiovascular morbidity. Serum Lp(a) levels have recently been associated with large artery atherosclerosis (LAA) stroke. We aimed to externally validate this association in an independent cohort. METHODS: This study stems from the prospective multicentre CoRisk study (CoPeptin for Risk Stratification in Acute Stroke patients [NCT00878813]), conducted at the University Hospital Bern, Switzerland, between 2009 and 2011, in which Lp(a) plasma levels were measured within the first 24 hours after stroke onset. We assessed the association of Lp(a) with LAA stroke using multivariable logistic regression and performed interaction analyses to identify potential effect modifiers. RESULTS: Of 743 patients with ischaemic stroke, 105 (14%) had LAA stroke aetiology. Lp(a) levels were higher for LAA stroke than non-LAA stroke patients (23.0 nmol/l vs 16.3 nmol/l, p = 0.01). Multivariable regression revealed an independent association of log10 Lp(a) with LAA stroke aetiology (aOR 1.47 [95% CI 1.03–2.09], p = 0.03). The interaction analyses showed that Lp(a) was not associated with LAA stroke aetiology among patients with diabetes. CONCLUSIONS: In a well-characterised cohort of patients with ischaemic stroke, we validated the association of higher Lp(a) levels with LAA stroke aetiology, independent of traditional cardiovascular risk factors. These findings may inform randomised clinical trials investigating the effect of Lp(a) lowering agents on cardiovascular outcomes. The CoRisk (CoPeptin for Risk Stratification in Acute Patients) study is registered on ClinicalTrials.gov. Registration number: NCT00878813.